Design and fabrication of a scalable liver-lobule-on-a-chip microphysiological platform - Banaeiyan, Amin A.; Theobald, Jannick; Wölfl, Stefan (Biofabrication, 2017)
The design and fabrication of a very large-scale liver-lobule (VLSLL)-on-a-chip device, providing a microphysiological niche for hepatocytes, is described. The device consists of an integrated network of liver-lobule-like hexagonal tissue-culture chambers constructed in a hybrid layout with a separate seed-feed network. As a key feature, each chamber contains a central outlet mimicking the central vein of a liver lobule. Separating chamber walls located between the culture area and feed network protects cells from the shear force of the convective flow. Arrays of designated passages convey nutrients to the cells by diffusion-dominated mass transport. We simulated the flow velocity, shear stress and diffusion of glucose molecules inside and outside the culture chambers under a continuous flow rate of 1 μ l min −1 . As proof of concept, human hepatocellular carcinoma cells (HepG2) were cultured for periods of 5 and 14 days and human-induced pluripotent stem cell (hiPSC)-derived hepatocytes for 21 days. Stabilized albumin secretion and urea synthesis were observed in the microfluidic devices and cells maintained morphology and functionality during the culture period. Furthermore, we observed 3D tissue-like structure and bile-canaliculi network formation in the chips. Future applications of the described platform include drug development and toxicity studies, as well as the modeling of patient-specific liver diseases, and integration in multi-organ human-on-a-chip systems.